Empowerment of Sekar Transad Women Farmers Group in Bandar Agung Village Through Digital Marketing Training (Pedial) - Agisti Tri'as Parawangzah; Dania Hellin Amrina; Dani Amran Hakim (Smart Society, 2021)
The development of the internet has influenced economic development. Therefore, it is necessary to understand business actors in implementing it. This community service activity is carried out in the form of training whose target is the Sekar Transad Women Farmers Group (KWT) regarding Digital Marketing (PEDIAL). The method used is to provide training to members of the Sekar Transad KWT, totaling 20 people, and held through the Zoom meeting application. As a result, KWT Sekar Transad members began to understand how to take good product objects, create attractive logo and packaging designs, and make sales using the Facebook and Instagram applications. In general, the basic capital owned by KWT Sekar Transad is quite good, then the potential for natural resources and village human resources is adequate, and the 4G internet network has reached various regions. Thus, the opportunity to apply the concepts described regarding PEDIAL is very possible. KWT members who take part in this training can alsp help other members or prospective business actors in running their business to make it easier and have a better impact.